2007
DOI: 10.1016/j.nucmedbio.2006.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial avid radioprobes. Preparation and evaluation of 7′(Z)-[125I]iodorotenone and 7′(Z)-[125I]iodorotenol

Abstract: The loss of mitochondrial function has been implicated in a number of maladies such as Huntington's Disease, Parkinson's Disease, cancer and cardiovascular disease. The objective of this research was to develop a radiolabeled mitochondrial probe. Two tracers, 7′-Z-iodorotenol and 7′-Z-iodorotenone, analogs of rotenone a natural product that inhibits Complex I of the mitochondrial electron transport chain, have been labeled with iodine-125 in 45-85% yield in a single step from the corresponding tribuytylstannyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…Images showed a rapid myocardial uptake soon after administration, with little or no interference from surrounding tissues such as the liver and lung. The heart/liver uptake ratio was similar to other rotenone-based MPI tracers 7′(Z)- 125 I-iodorotenol and 7′(Z)- 125 I-iodorotenone [12], as well as the benchmark agent 99m Tc-sestamibi [13]. Heart/stomach and heart/intestine ratios remained moderate within the first 1 h post-injection of the tracer, which allow for a good imaging window.…”
Section: Discussionsupporting
confidence: 65%
“…Images showed a rapid myocardial uptake soon after administration, with little or no interference from surrounding tissues such as the liver and lung. The heart/liver uptake ratio was similar to other rotenone-based MPI tracers 7′(Z)- 125 I-iodorotenol and 7′(Z)- 125 I-iodorotenone [12], as well as the benchmark agent 99m Tc-sestamibi [13]. Heart/stomach and heart/intestine ratios remained moderate within the first 1 h post-injection of the tracer, which allow for a good imaging window.…”
Section: Discussionsupporting
confidence: 65%
“…7'-Z-iodorotenone (ZIROT) is an inhibitor of complex I of the mitochondrial transport electron chain that has been labeled with 125 I. Z-iodorotenone is a neutral and lipophilic compound and has been shown to have high first-pass extraction (~84%) and better retention in comparison to sestamibi (~48% first-pass extraction) in isolated perfused rabbit heart studies [26]. While the absolute heart uptake of iodorotenone was similar to that of sestamibi and tetrofosmin, ZIROT demonstrated significantly superior (P<0.001) heart-to-lung ratios in rodents at 1 h post-injection [27]. However, biodistribution experiments in adult male Sprague-Dawley rats indicated that Z-iodorotenone heartto-liver ratio was similar to that of sestamibi but signifi- Fig.…”
Section: Future Perspectives Of Spect Perfusion Tracersmentioning
confidence: 99%
“…Furthermore, comparisons of the initial 5-minute imaging with the 60-minute imaging demonstrated different results from the simple "uptake/retention" rest-stress model. Other investigators have noted similar differences between 5 minute and 60 minute imaging of the heart (Hurwitz 1993, Saha 1994, Giubbini 1995, Pace 2005) allowing for enhanced detection of congestive heart failure (Hurwitz 1998, Kumita 2002, Sugiura 2006, Matsuo 2007, cardiomyopathies (Meissner 2002, Ikawa 2007), Prinzmetal 's angina (Ono 2002(Ono , 2003 and underlying coronary artery disease (Meerdink 1990, Richter 1995, Shin 1995, Takeishi 1996, Takahashi 1996, Fujiwara 1998, Hurwitz 1998, Ayalew 2000, Liu 2001, Kumita 2002, Tanaka 2006, Fukushima 2007, VanBrocklin 2007 including evidence of wash-in (Meerdink 1990, Richter 1995 indicative of critical lesions not detected by conventional MPI. In the same way that thrombolysis in myocardial infarction (TIMI) flow is used to look for changes (sometimes subtle, sometimes not) in coronary blood flow in the catch lab, multiple imaging following pharmacologic or EST allows us to take a more advanced look at the physiologic function of the heart, unmasking ischemic heart disease missed by rest-stress imaging.…”
Section: Fleming-harrington Redistribution Wash-in Washout (Fhrww)mentioning
confidence: 85%